Management of Recreational Areas. The Impact of Management of the Development of Shchuchinsko-Borovsky Resort Area on the Improvement of the Level of Financial and Economic Sustainability in the Region - BOKENCHIN, Kazbek Kuandykovich; ALTAY, Marat; SHAIMERDENOVA, Aigul; BOKENCHINA, Laura Kurymbaevna; DABYLOVA, Bibigul (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The formation and development of the recreation system generate a range of problems associated with the need to manage the development of recreational areas, which demonstrate the properties of complex environmental and economic systems. For this reason, it is critically important to improve the environmental and economic efficiency of recreational areas through the formation of an effective management system, especially in the aspect of the balanced spatial development of regions. The paper presents an analysis of various methodological approaches to the management of recreational areas, defines the stages of implementation of recreational area management, and offers a recommended recreational area zoning scheme and the corresponding recreational area management structure based on the example of the Shchuchinsko-Borovsky resort area. The results of the study suggest that recreational area management should be considered as an activity of public authorities to create conditions for the rational and effective use of the recreational potential of the region, and the adoption of rational and balanced managerial decisions can only be ensured by the establishment of a cadastre of recreational resources.